2008
DOI: 10.1016/j.pubrev.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

More than just the media: Considering the role of public relations in the creation of sporting celebrity and the management of fan expectations

Abstract: This article considers the complex nature of sporting celebrity and the role of media and public relations in the creation of both sports celebrity and the fan expectations associated with that celebrity. While public relations literature has traditionally considered PR as a promotion and communication tool, this article acknowledges that in the cultural and ideological world of sport, PR has a much more sophisticated role to play. In the event of either positive or negative media attention, a sporting celebri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 5 publications
1
30
0
2
Order By: Relevance
“…Specifically, for the participants in the three countries where the data were collected, mass media, social media, major sport events, and video games were identified as media sources that increase fans' awareness. These findings are consistent with those reported by Summers and Johnson 54 , thereby suggesting the important role of mass media in the process of creating and spreading an athlete's good image. Sierra, Taute, and Heiser 55 mentioned that social media helps generate interest in and deepens fans' knowledge about athletes.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, for the participants in the three countries where the data were collected, mass media, social media, major sport events, and video games were identified as media sources that increase fans' awareness. These findings are consistent with those reported by Summers and Johnson 54 , thereby suggesting the important role of mass media in the process of creating and spreading an athlete's good image. Sierra, Taute, and Heiser 55 mentioned that social media helps generate interest in and deepens fans' knowledge about athletes.…”
Section: Discussionsupporting
confidence: 92%
“…Other research findings have observed more complex reactions that contradict such a linear endorser blame‐brand evaluation relationship (Summers & Morgan, ). Early work by Lerner and Miller () suggests that to avoid the consideration whereby negative events can fall on innocent people, consumers may actually lower their opinion of the person so that they seem deserving of a bad fate.…”
Section: Adverse Influence Of Negative Publicitymentioning
confidence: 90%
“…Evidence of transparency and consistency were accomplished in this study with the use of a pre-designed contact summary sheet to record all steps and dates followed in this study; and to summarize the lists of websites used. This consistency and transparency of data management helped to address the validity in the research program (27).…”
Section: Methodsmentioning
confidence: 99%